2004
DOI: 10.1111/j.1471-0528.2004.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Are women's expectations and preferences for intrapartum care affected by the model of care on offer?

Abstract: Objective To investigate the effect of service provision on consumer preferences, in particular, whether women who have access to systems of care which offer particular attributes (such as continuity of carer) value these attributes more highly than women for whom the attributes are not a realistic option. Design Simple rating scales and a discrete choice experiment were used to assess the importance to women of different aspects of intrapartum care. Sample and setting The sample consisted of 301 women at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 31 publications
7
50
0
3
Order By: Relevance
“…Clarke et al [46] recommend elicitation of patient views on completion of the care process or once they are sufficiently informed to make a judgement. However, Hundley and Ryan [47] and Ryan et al [13] have found that experience and knowledge of the availability of certain aspects of care influence patient preferences and patients report preferences for current service provision. Finally, this study has the limitation of a small sample of patients from which choices were elicited.…”
Section: Cost-consequences Analysismentioning
confidence: 98%
“…Clarke et al [46] recommend elicitation of patient views on completion of the care process or once they are sufficiently informed to make a judgement. However, Hundley and Ryan [47] and Ryan et al [13] have found that experience and knowledge of the availability of certain aspects of care influence patient preferences and patients report preferences for current service provision. Finally, this study has the limitation of a small sample of patients from which choices were elicited.…”
Section: Cost-consequences Analysismentioning
confidence: 98%
“…1 Research into how women and their families make decisions about where to give birth has tended to focus on home and OUs, with the following factors being consistently important to women: finding a balance between safety and a satisfactory birth experience, the influence of friends, family and doctors, social class and cultural values, 54,55 and the model of care on offer. 56 More recent work has found that women value birth centre care, particularly the environment, personal attention, calm ambience and close to obstetric support if needed, 51,[57][58][59] in essence what is often perceived as 'the best of both worlds'. 58 Longworth et al 60 found that women who chose a home birth valued continuity of care, a homely environment and the ability to make their own decisions regarding interventions.…”
Section: Efficacy and Effectivenessmentioning
confidence: 99%
“…4 It has been suggested that the care options available to women influence their preferences for intrapartum care, indicating that the choice of birthing positions in the second stage of labour may be determined more by midwives' advice than by women's personal preferences. 5,6,7 In a recent Cochrane review it was suggested that the influence of midwives on the positions adopted by women during labour and birth, can be regarded as inconsiderate of women's comfort and disempowering. 2 It is well documented that women who have choices and are involved in decision making during labour and birth have an increased sense of control, which optimizes their birth experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Hundley et al 6 concluded that for 40 % of the women the most important attribute was involvement in decision-making. Very little scientific investigation has considered women's decision-making and preferences for birth positions in the second stage of labour.…”
Section: Introductionmentioning
confidence: 99%